Dakwah Message in The Film 172 Days, Adopted From a Novel by Nadzira Shafa - Oktika, Mi'raj Dini; Soiman, Soiman (Pusat Studi Aswaja An-Nahdliyyah UNISNU Jepara, 2024)
This da'wah activity is increasingly spreading to the world of film, including the film 172 Days. The film tells the story of the migration journey of a young woman who experiences difficult times in her life, including mental problems that lead her away from religion. For this reason, the author conducted an in-depth study of the film 172 days in order to understand the preaching messages contained in the film. The aim of this research is to analyze da'wah messages related to Aqidah, sharia and morals. The theoretical benefits of this research can be a reference for future writers and provide insight into knowledge about da'wah. Practically, it is hoped that this research can motivate preachers to make more use of film media. The author uses library research with qualitative methods. Content Analysis is a qualitative research technique that emphasizes the regularity of communication content, the meaning of communication content, the reading of symbols, and the meaning of symbolic interactions that occur in communication. The results of this research reveal that there is a da'wah message that includes aspects of Aqidah, sharia and morals. The Aqidah message found includes faith in Allah and belief in the last day. Moral messages include behavior towards God, oneself and family. Meanwhile, the message of sharia includes aspects of worship of Allah and muamalah relationships.